Mitigasi Risiko Bahaya Listrik pada Operasional Dredger melalui Pelatihan Dasar K3 bagi Operator Tambang di Wilayah Perairan - Bhima Satria Rizki Sugiono; Diky Djafar Sidik (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Dredger operations in water-based mining areas have a high occupational risk because they involve a combination of wet environments, mechanical equipment, and electrical systems. The presence of electrical panels, power cables, terminal connections, electric motors, inverters/drives, and protection components on the Dredger requires a sound understanding of Occupational Health and Safety, particularly electrical safety. Water splashes, wet walking surfaces, high humidity, and improper procedures during inspection or cleaning may increase the risk of short circuits, protection trips, and electric shock. Therefore, structured basic safety training is required so that operators are able to identify electrical hazards and implement safe working procedures. This activity aimed to improve operators’ understanding of hazardous electrical components, initial safety briefing procedures, measurement practice and safe handling during trips or short-circuit indications, and the correct and safe use of water pumps for unit cleaning. The activity was carried out through field observation, technical briefing, direct demonstration on the electrical panel and work area, simple measurement practice, and safe cleaning practice. The results indicate that field documentation can serve as an effective learning medium to strengthen operators’ understanding of electrical hazard sources on the Dredger, the application of simple lock out-tag out procedures, the control of wet areas, and the limitation of water spray direction during cleaning activities. Overall, the activity shows that improved compliance with safety procedures may reduce the risk of short circuits and electric shock during operation and maintenance.